Candida Glabrata Pneumonia in Post COVID-19 Patient: A Rare Case Report - Jahja Teguh Widjaja; Evelyn Nathania (Jurnal Respirologi Indonesia, 2023)
Background: One of the issues in post COVID-19 is secondary infection and fungal infection is one of the complications that must be detected at early stage to prevent. Early detection to prevent underdiagnosed and undertreatment. Candida glabrata, one of the pathogens in fungal infection is rare and can acts as infectious agent with immunocompromised patients.Case: A 69-year-old man came to hospital with major complaints of cough and shortness of breath for five days. He was diagnosed COVID-19, After completed treatment the nasopharyngeal PCR swab show negative result for COVID-19. After being discharged, he did several chest X-ray examinations with progressively worsening cough. Chest CT-Scan revealed consolidations and cavity. Sputum culture was positive for Candida glabrata and negative for BTA. He received echinocandins as anti-fungal treatment, which inhibits enzymes that is necessary for fungi’s cell wall synthesis, shows clinical and radiological improvement.Discussion: COVID-19 affect immune system which resulting higher risk for secondary infection. The use of broad-spectrum antibiotics, immune-suppression of the host, and use of medical devices are major risk factors for Candida infections. Meanwhile C. Albicans is still the most common cause of fungal pneumonia by Candida, we should consider C. glabrata as one of its pathogens. Conclusion: COVID-19 affects many aspects in our life, even after we treat the main problem, some patients manifest symptoms later. Diagnosing fungal infection especially invasive candidiasis is quite challenging with higher mortality rate. Not only C. glabrata more uncommon than C. albicans, but also it was one of difficult to treat pathogens.